Influence of Product Placement in Children’s Movies on Children’s Snack Choices - Brown, Callie L. (Appetite, 2017)
BACKGROUND: Media exposure affects health, including obesity risk. Children’s movies often contain food placements—frequently unhealthy foods. However, it is not known if these cues influence children’s food choices or consumption after viewing. We explored whether children’s snack choices or consumption differs based on: 1) recent exposure to movies with high versus low product placement of unhealthy foods; and 2) children’s weight status. METHODS: Children ages 9–11 were assigned to watch a high (“Alvin and the Chipmunks,” n=54) or low (“Stuart Little,” n=60) product-placement movie. After viewing, participants selected a snack choice from each of five categories, several of which were specifically featured in “Alvin.” Uneaten snacks from each participant were weighed upon completion. Snack choice and amount consumed by movie were compared by t-tests, and differences in snack choices by movie were tested with logistic regression. RESULTS: Participants consumed an average of 800.8 kcal; mean kcal eaten did not vary by movie watched. Participants who watched the high product-placement movie had 3.1 times the odds (95% CI 1.3–7.2) of choosing cheese balls (most featured snack) compared to participants who watched the low product-placement movie. Children who were overweight or obese consumed a mean of 857 kcal (95% CI: 789–925) compared to 783 kcal (95% CI: 742–823, p=0.09) for children who were underweight or healthy weight. Children’s weight status did not significantly affect their choice of snack. CONCLUSIONS: Branding and obesogenic messaging in children’s movies influenced some choices that children made about snack foods immediately following viewing, especially food with greatest exposure time in the film, but did not affect total calories consumed. Future studies should examine how the accumulation of these messages affects children’s long-term food choices.